Personal Protective Equipment (PPE) Quick Reference Guide for Low Volume Citrus Applications - Steve H. Futch; Lukasz L. Stelinski; Michael E. Rogers; Jamie D. Yates (EDIS, 2010)
CH203, a one-page fact sheet by S.H. Futch, L.L. Stelinski, M.E. Rogers and J.D. Yates, provides a table describing personal protective equipment requirements for several products used in citrus production. Published by the UF Department of Entomology and Nematology, September 2009.